Pendekatan Ekspresionisme pada Penyutradaraan Film “Hari Yang Tadi” - Andre Buttiamal Dani Damanik; Surya Darma (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
This thesis explains about the directing of the film Hari Yang Tadi which uses an expressionist style to present an approach in the film that depicts emotions and subject4e experiences, not physical reality. The film Hari Yang Tadi tells the story of a daughter who is disobedient to her mother and as a result the daughter experiences the phenomenon of deja vu (repeated events). The methods used in the film Hari Yang Tadi are the methods of preparation, elaboration, synthesis, realization, and completion. The theory used in this thesis is directing with an expressionist style which is applied in several aspects of the film, such as scenes that emphasize emotional communication, artistic direction, cinematography, sound design, coloring and image editing. The technical concepts contained in this work are pre-production, production, and post production. The duration of the creation of this thesis is three years starting from November 2022 to January 2025. The result of the creation of this thesis is the application of an expressionist style in the film Hari Yang Tadi such as changes in expression, emotion, artistic direction, costume design, sound design and coloring. The conclusion in this thesis is that the direction is in an expressionist style that is filled with an atmosphere of emotional changes in the main character that is not a physical reality